Promoting Four Corners Strategy to Improve Secondary School Students' Speaking Skills - Rista Junita; Rahma Dianti; Nita Ria (Didascein : Journal of English Education, 2024)
Four Corners is a cooperative learning strategy that drives students to think things through carefully before sharing them with others. This strategy encourages the students to express their thoughts, opinions, and feelings with their peers by creating four opinion corners: strongly agree corner, agree corner, strongly disagree corner, and disagree corner. This research aimed to investigate the effectiveness of the four corners strategy in enhancing secondary school students’ speaking achievement and compare the students’ speaking achievement between the experimental group and the control group. The researchers employed a quasi-experimental design. 168 students made up the entire population. The research participants were chosen using purposive sampling. 64 students participated as the sample, divided into experimental and control groups. An oral test about asking and giving opinions was used to gather the data. The test was administered twice. The Wilcoxon Signed Rank Test and the Mann-Whitney U Test were used to analyze the data since the data were not normally distributed. The results of the Wilcoxon Signed Rank test revealed that the students showed a considerable improvement in speaking skills when employing the Four Corners strategy. The results of the Mann-Whitney U test showed that students’ speaking abilities who got intervention using the Four Corners strategy were better than the students who did not receive the intervention using the Four Corners strategy.